Workload analysis with the full time equivalent method approach to determine workforce required - Sonny Taufan; Risca Rahmawati; Mujiyono Mujiyono; Donant Alananto Iskandar (Jurnal STEI Ekonomi, 2023)
This research aims to to analyse the workload using the Full Time Equivalent (FTE) method to produce the optimal number of human resources. The post-pandemic economic recovery has led to increased productivity in various sectors, including PT Mada Wikri Tunggal which has experienced an increase in sales in the last three years. However, this increase in sales is inversely proportional to the number of human resources in the office sector of the company. Excessive or too minimal workload will cause inefficiency in the productivity of a company. The amount of workload that is too heavy indicates that the amount of workforce available is not balanced with the workload given, so it can cause physical and mental fatigue which results in a decrease in productivity. The data analysis method used in this research is the Full Time Equivalent (FTE) method. FTE can be assumed as a measure of the time required for the workforce to completely carry out work activities. Note: This article serves as a restored version of the original content following a corruption incident. The Digital Object Identifier (DOI) has been successfully re-registered and reactivated to ensure continued accessibility and citation integrity.